Pemberdayaan Kader Dalam Pemantauan Kejadian Hipertensi Pada Lansia di Masyarakat - Sri Wahyuni, Endang; Hastuti Prasetyaningsih, Roh; Febri Arifiati, Retna (Poltekkes Kemenkes Surakarta, 2024)
Background: Hypertension in the elderly is a silent killer condition that occurs due to the aging process. This needs attention because many elderly people are not aware of the signs or symptoms that appear. This community service activity aims to improve cadres' knowledge, abilities, and skills in handling hypertension in the elderly through counselling and training activities. It will also increase the knowledge and understanding of the elderly regarding hypertension. The benefits of this activity are expected to be used as promotive and preventive activities in improving community empowerment programs in sustainable health. Methods: This community service uses counselling and training activities. Counselling and training were carried out at the Elderly Posyandu, Ngargorejo Village, Boyolali, Central Java, using the total sampling technique. The results of the understanding and skills of cadres and the elderly were evaluated using questionnaires before and after counselling. Results: There were changes in the knowledge and skills of cadres and the elderly in monitoring the occurrence of hypertension. The average level of expertise of cadres and the elderly before counselling was 8.73, and after counselling, 9.77. There was an increase in the average value of 1.04. The results of the paired sample t-test showed a ρ value of 0.001. Conclusion: The provision of training and counselling on the level of knowledge of cadres and the elderly about hypertension is an influence. It is hoped that posyandu cadres and the elderly can work together to prevent and control hypertension in the community.